The antecedents, regulation and maintenance of anger on the road: A qualitative investigation on the factors influencing driver anger and aggression. (February 2023) - Love, Steven; Truelove, Verity; Rowland, Bevan; Kannis-Dymand, Lee; Ross, Dyann; Sullman, Mark; Davey, Jeremy
Highlights: Discrepancies between drivers' attributes triggered and amplified aggression. Risk perceptions were generally low and resistant among trait aggressive drivers. Metacognitive awareness played a significant role in self-regulatory ability. Cognitive, attentional and emotion regulation were attributed to reduce aggression. Rumination styles were perceived to influence future driving behaviours. Abstract: Aggressive driving behaviour (ADB) is an ongoing road safety issue that has proven difficult to deter. The purpose of this study was to: qualitatively investigate the antecedents of ADBs, document the self-regulatory processes and metacognitive beliefs associated with ADBs, and explore how metacognitive facets might influence the progression and expression of anger. An online sample of Queensland (Australia) motorists who had recently engaged in ADBs ( N  = 34) were interviewed and inductive thematic analysis was applied to the response data. The results showed that firstly, ADBs were primarily triggered by discrepancies in drivers' mentality. Several perceptual, situational, internal and experiential factors were found to influence the likelihood and severity of the response to the triggering behaviour. Trait aggressive drivers tended to have lower perceptions of risk, and resistance to deterring events (e.g., fines; near misses). The self-regulation of ADBs appeared to be contingent on participants' metacognitive awareness to recognise when their behaviour was being influenced by anger, and the ability to utilise appropriate cognitive-behavioural regulatory strategies when required. Following ADBs, participants reported different forms of evaluation, including anger, depressive, fearful, and reflective rumination styles, and these processes were perceived to influence future driving behaviours in different ways. However, trait aggressive drivers in particular tended to demonstrate a lack of evaluation following ADBs. The findings of this study may provide a framework for future research applying the concept of self-regulation to the topic of ADB and may also help inform road authorities of alternative and effective approaches for reducing driver aggression.